Somos mulheres, não somos feministas: a presença digital das deputadas conservadoras e a equidade de gênero (2023-2024) - Rosseto, Lourdes Maria Porto (Universidade Federal de São Carlos, 2026)
This research investigates how neoconservative female parliamentarians re-elected in 2022 update their agenda in the digital environment regarding themes related to gender equity following the defeat of President Jair Messias Bolsonaro. The general objective of the study is to analyze how these women instrumentalize female identity as a strategic resource to promote neoconservative political views and delegitimize gender equity policies. To this end, the Instagram profiles of Congresswomen Bia Kicis and Carla Zambelli, both from the Liberal Party (PL), are analyzed during the 2023-2024 biennium. The methodology is anchored in Computational Social Science, employing Natural Language Processing (NLP) techniques, social network analysis, and multimodal qualitative analysis. The results indicate that, contrary to the cooling-off hypothesis, the patriotic and nationalist agenda remains central, strategically merging with family and religion agendas. A division of discursive labor is observed: while Carla Zambelli mobilizes engagement through political and affective maternalism, Bia Kicis operates a strategic legalism to contest democratic institutions. It is concluded that the digital mandate of these parliamentarians instrumentalizes "womanhood" and moral panic as tools for base cohesion and the maintenance of gender hierarchies, adapting resiliently to the opposition context.
We are women, we are not feminists: the digital presence of conservative congresswomen and gender equity (2023-2024)
Keywords: Bia Kicis; Carla Zambelli; Gênero; Política digital; Neoconservadorismo; Gender; Digital politics; Neoconservatism; CIENCIAS HUMANAS::CIENCIA POLITICA::COMPORTAMENTO POLITICO; 5. Igualdade de Gênero